Type 2 MI induced by a single high dose of isoproterenol in C57BL/6J mice triggers a persistent adaptive immune response against the heart. - Forte,E; Panahi,M; Baxan,N; Ng,FS; Boyle,JJ; Branca,J; Bedard,O; Hasham,MG; Benson,L; Harding,SE; Rosenthal,N; Sattler,S (J Cell Mol Med, 2021)
Heart failure is the common final pathway of several cardiovascular conditions and a major cause of morbidity and mortality worldwide. Aberrant activation of the adaptive immune system in response to myocardial necrosis has recently been implicated in the development of heart failure. The ß-adrenergic agonist isoproterenol hydrochloride is used for its cardiac effects in a variety of different dosing regimens with high doses causing acute cardiomyocyte necrosis. To assess whether isoproterenol-induced cardiomyocyte necrosis triggers an adaptive immune response against the heart, we treated C57BL/6J mice with a single intraperitoneal injection of isoproterenol. We confirmed tissue damage reminiscent of human type 2 myocardial infarction. This is followed by an adaptive immune response targeting the heart as demonstrated by the activation of T cells, the presence of anti-heart auto-antibodies in the serum as late as 12 weeks after initial challenge and IgG deposition in the myocardium. All of these are hallmark signs of an established autoimmune response. Adoptive transfer of splenocytes from isoproterenol-treated mice induces left ventricular dilation and impairs cardiac function in healthy recipients. In summary, a single administration of a high dose of isoproterenol is a suitable high-throughput model for future studies of the pathological mechanisms of anti-heart autoimmunity and to test potential immunomodulatory therapeutic approaches.